2019
DOI: 10.1186/s12887-019-1750-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B infection and risk factors among children living with HIV in Yaounde, Cameroon: an integrated management

Abstract: BackgroundThe endemicity of hepatitis B virus (HBV) prompted the systematic immunization of newborns in Cameroon since 2005. In the frame of a considerable burden of HIV/HBV co-infection (17.5%), monitoring HBV among children living with HIV (CLHIV) would guide toward HIV/HBV integrated paediatric care. We sought to ascertain the prevalence and determinants of HBV infection in the population of CLHIV and performance of commonly used rapid diagnosis tests (RDTs).MethodsCross-sectional study conducted from Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The result of this study reveals a higher positivity rates of HBsAg compared to results reported by investigators from West Africa (2.2-5.3%) [20,[35][36][37][38] and comparable positivity rates of anti-HCV (0.5-3.9%) results from the same region [20,37,39].…”
Section: Discussionsupporting
confidence: 60%
“…The result of this study reveals a higher positivity rates of HBsAg compared to results reported by investigators from West Africa (2.2-5.3%) [20,[35][36][37][38] and comparable positivity rates of anti-HCV (0.5-3.9%) results from the same region [20,37,39].…”
Section: Discussionsupporting
confidence: 60%
“… 37 While 70% of the global HIV burden is found in SSA, HBV is very prevalent within the Asian (15%) and African populations (8–40%). 38 Even though Cameroon is experiencing declining trends of HBV infections (12% to 11% in 2019) among adults and adolescents aged 15–49 y, 38 the country is still experiencing a generalized epidemic of HBV infections, suggesting the need for evidence-based strategic interventions. This high endemicity seems to be concentrated only in adults (11%), 39 healthcare workers (HCWs) (9%) 40 and pregnant women (8%), 41 as a recent study reported a moderate prevalence of 2% in the pediatric population with similar pattern reported in Ethiopia, Democratic republic of Congo, Tanzania, and Malawi.…”
Section: Hepatitis B Infectionmentioning
confidence: 99%
“…This high endemicity seems to be concentrated only in adults (11%), 39 healthcare workers (HCWs) (9%) 40 and pregnant women (8%), 41 as a recent study reported a moderate prevalence of 2% in the pediatric population with similar pattern reported in Ethiopia, Democratic republic of Congo, Tanzania, and Malawi. 38 This relatively moderate pediatric HBV prevalence could be attributed in part to the wide pediatric coverage of anti-HBV vaccination in Cameroon. Similarly, global reports have stated that universal vaccination has globally decreased HBsAg prevalence in children younger than 5 y from 5% in the pre-vaccination era (1980s to early 2000s) to 1% in 2015.…”
Section: Hepatitis B Infectionmentioning
confidence: 99%
“…To gain an understanding of feasibility and acceptability from the perspective of patients and care providers, we qualitatively explored views relating to how feasible it is to integrate and how acceptable this integrated HIV/ HBV care model is, as well as the likely influential factors. Although some countries have mentioned the possibility of exploring HBV/HIV care integration, [10][11][12] fewer have actually taken steps to implement integration. This exposes a void in information on the experience and practice of providing integrated care that is holistic for both HIV-and HBV-infected persons.…”
Section: Introductionmentioning
confidence: 99%